Neuromuscular and Biomechanical Adaptations of the Lower Limbs During the Pre-Landing and Landing Phase of Running Under Fatigue Conditions - Bocheng Chen; Jiaxin Wu; Jingyuan Jiang; Guoxiang Wang (Applied Sciences)
Objective: Our objective was to investigate the biomechanical and neuromuscular adaptations of the lower limbs during the landing phase of running under fatigue conditions. Methods: A controlled fatigue protocol was used to induce running-related fatigue in participants. Data were collected using a three-dimensional motion capture system, force platform analysis, and surface electromyography (sEMG). Kinematic variables, such as hip, knee, and ankle joint angles and range of motion, were analyzed alongside kinetic parameters, including vertical ground reaction forces (vGRFs) and joint moments. sEMG was used to measure the muscle activation levels of the rectus femoris, biceps femoris, tibialis anterior, and gastrocnemius, and to calculate antagonist coactivation ratios. Statistical analyses were performed to assess the differences in pre- and post-fatigue using paired t-tests, with a significance level set at α = 0.05, and FDR correction was applied to control for multiple comparisons. Results: Post-fatigue, hip and knee flexion angles at initial contact decreased by 4.5% and 4.8%, respectively (FDR-adjusted p = 0.023, 0.0157), while their range of motion increased significantly by 10.4% and 11.1% (FDR-adjusted p = 0.0115, 0.0063). The second vGRF peak increased by 2.1% post-fatigue (FDR-adjusted p = 0.0086), with no significant changes in the first vGRF peak (p > 0.05). Muscle activation levels significantly increased in the rectus femoris (10.7%), biceps femoris (8.3%), tibialis anterior (9.1%), and gastrocnemius (10.2%) (FDR-adjusted p < 0.05). The antagonist coactivation ratio significantly decreased in the early and late landing phases (FDR-adjusted p = 0.0033, 0.0057), reflecting neuromuscular adjustments to fatigue. Conclusions: Fatigue-induced adaptations in joint kinematics, muscle activation, and coactivation strategies optimize performance and stability but may increase mechanical stress on lower-limb joints, highlighting a need for targeted interventions to mitigate injury risk.